2019
DOI: 10.12680/balneo.2019.273
|View full text |Cite
|
Sign up to set email alerts
|

Correction of magnesium deficiency in the body with balneological means: experimental studies

Abstract: In the modern world, a lack of magnesium in the body is one of the most common deficient conditions in humans. Low levels of magnesium have been associated with a number of chronic diseases. This work is devoted to the study of the effect of the use of the balneological means "Magnesium oil" for the correction of the manifestations of experimentally induced magnesium deficiency. The experiment was conducted on 50 white female rats of the Wistar auto-breeding line which were divided into 3 equal groups: (1) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous research has also identified low intake of Mg with WL diets, providing between 55 and 86 % of requirements (25) and are typically low carbohydrate (25,104) . Mg is a mineral and common intracellular cation involved in energy production, protein synthesis, muscle and nerve function and bone health (118)(119)(120) . Prolonged inadequate intake of Mg has been associated with low Ca levels, a risk factor for osteoporosis in postmenopausal females and low-grade inflammation (118)(119)(120) .…”
Section: Micronutrient Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also identified low intake of Mg with WL diets, providing between 55 and 86 % of requirements (25) and are typically low carbohydrate (25,104) . Mg is a mineral and common intracellular cation involved in energy production, protein synthesis, muscle and nerve function and bone health (118)(119)(120) . Prolonged inadequate intake of Mg has been associated with low Ca levels, a risk factor for osteoporosis in postmenopausal females and low-grade inflammation (118)(119)(120) .…”
Section: Micronutrient Profilementioning
confidence: 99%
“…Mg is a mineral and common intracellular cation involved in energy production, protein synthesis, muscle and nerve function and bone health (118)(119)(120) . Prolonged inadequate intake of Mg has been associated with low Ca levels, a risk factor for osteoporosis in postmenopausal females and low-grade inflammation (118)(119)(120) .…”
Section: Micronutrient Profilementioning
confidence: 99%
“…More is known about the biological and therapeutic effects of silicon MWs, including in balneology (when used for drinking and bathing), which results in enterosorption, adhesion of microorganisms, normalisation of lipid peroxidation/ antioxidant protection balance and modulating effect on baro-and chemoreceptors (external use) [25][26][27][28][29][30]. The data on the biological action and impact on human health of such a trace element as boron should also be considered [26,30,[31][32][33][34][35]. In this aspect, the concept of hormesis and the role of hormesis in hydrothermal treatments should be mentioned [36].…”
Section: клінічна та експериментальна медицина / Clinical and Experim...mentioning
confidence: 99%
“…Analyzing the literature data, we found that MW with a sufficient content of bicarbonates, chlorine, sodium, potassium ions, and trace elements have lipid-lowering, hepatotropic, and cardioprotective properties, which is pathogenetically substantiated in the treatment of patients with chronic hepatitis C with concomitant NAFLD [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%